2016
DOI: 10.1186/s12940-016-0157-5
|View full text |Cite
|
Sign up to set email alerts
|

Associations between microvascular function and short-term exposure to traffic-related air pollution and particulate matter oxidative potential

Abstract: BackgroundShort-term exposure to ambient air pollution has been associated with acute increases in cardiovascular hospitalization and mortality. However, causative chemical components and underlying pathophysiological mechanisms remain to be clarified. We hypothesized that endothelial dysfunction would be associated with mobile-source (traffic) air pollution and that pollutant components with higher oxidative potential to generate reactive oxygen species (ROS) would have stronger associations.MethodsWe carried… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 57 publications
0
38
0
Order By: Relevance
“…Transition metals (eg, V, Fe, Co, Ni, Cu, Zn) from various sources have been associated with ROS generation, oxidative stress, and inflammation both in vitro and in human studies, [54][55][56]75,76 among other effects. Their redox activity is thought to stimulate cellular ROS production, eventually leading to oxidative stress and inflammation.…”
Section: Pahs and Trace Elementsmentioning
confidence: 99%
“…Transition metals (eg, V, Fe, Co, Ni, Cu, Zn) from various sources have been associated with ROS generation, oxidative stress, and inflammation both in vitro and in human studies, [54][55][56]75,76 among other effects. Their redox activity is thought to stimulate cellular ROS production, eventually leading to oxidative stress and inflammation.…”
Section: Pahs and Trace Elementsmentioning
confidence: 99%
“…Inverse associations have been observed between RHI and important risk factors for CVD, such as diabetes, obesity, smoking, and the ratio between total and HDL cholesterol (Hamburg et al 2008). Associations with PM exposures have been somewhat inconclusive: Decreased RHI was associated with increased air pollution exposure in elderly (Bräuner et al 2008a;Zhang et al 2016), but not in younger people (Bräuner et al 2008b;Li et al 2015;Ljungman et al 2014). Exposures to ambient air pollution mixtures showed associations with BPA, but not with hyperemic response to ischemia (Ljungman et al 2016).…”
Section: Rhi Vs Bpamentioning
confidence: 99%
“…Previous studies have revealed that different size ranges of PM can be emitted from various sources with different fingerprints [10,11]. PM from different sources might have different toxicological characteristics as well as different impacts on visibility, and radiative forcing, supporting the postulation that PM mass concentration is not the most appropriate metric to investigate the adverse effects of PM [12,13]. Therefore, source apportionment studies are quite beneficial in identifying different sources of PM, their corresponding chemical compositions and their link with toxicity, which can further be used by health authorities to develop policies to mitigate the detrimental health impacts of exposure to ambient PM.…”
Section: Introductionmentioning
confidence: 99%